Proposed Amendments to the Constitution of the International Commission on Zoological Nomenclature - Nomenclature, International Commission On Zoological (European Journal of Taxonomy, 2020)
The International Commission on Zoological Nomenclature (ICZN) proposes amendments to its Constitution and solicits constructive feedback from the zoological community. In compliance with the Constitution, the proposed amendments are made broadly available, and there will be a one-year period for submission of comments starting on 30 April 2020. The amendments may be modified in the light of the comments, before the final version is voted on by the Commissioners.